An Analytical Study On The Interrelationships Between Tourist Influx And Prevailing Security In The Kamalabari Area Of Majuli District, Assam (Journal of Namibian Studies : History Politics Culture, 2023)
Tourism inflow and outflow can be significantly impacted by prevailing security in a place. The present study is an attempt to address the condition of security condition in Kamalabari region of Majuli. The current research is encompassed along with qualitative method of analysis. The primary data are gained through a schedule and secondary data are also collected to fulfill the objective. Remote sensing techniques and GIS have been applied to get better understanding about the study area. The study endeavors to find out whether security condition impact on tourist inflow or not. The findings suggest that improving and solve the tourism related problems will lead Majuli to be a finer tourist place. The present study cleared that the relationship between the tourist influx and the tourist security in the Kamalabari area, Majuli is directly proportionate rather than inversely proportionate.